Mais desoneraç\~ao, mais inovaç\~ao? Uma avaliaç\~ao da recente estratégia brasileira de intensificaç\~ao dos incentivos fiscais a pesquisa e desenvolvimento - Glauter Rocha; André Rauen (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The aim of this paper is to evaluate from 2008 on the effects of Brazilian government strategy of R&D tax incentives increase. We used the synthetic control method to estimate its causal impacts from 2010 to 2015. We demonstrated that this strategy had no relevant effect on research and development (R&D) private investment. Despite the substantial increases in tax reductions, it did not leveraged private expenditures. Actually, it helped to produce a policy mix (direct versus indirect support) not effective, which slightly decreased private spending, in comparison to what would have happened without the escalating fiscal incentives.
Keywords: O310; 330; innovation; R&D; tax incentives; synthetic control method